THE EFFECT OF DISTILLATE STORING DISTILLED FROM FRUCTOSE SYRUPS TOWARD ITS ACETALDEHYDE CONCENTRATION MEASURED BY GAS CHROMATOGRAPHY - Maria Monica Sianita Basukiwardojo (Universitas Gadjah Mada, 2005)
Acetaldehyde is a compound of aldehyde group that is very volatile and toxic. This compound can be found in fructose syrups used in carbonate beverages. The syrups had been distilled then analysed using gas chromatography. The concentration of acetaldehyde was 289.78 g/g in the distillates kept for one week, 295.30 g/g in those kept for two weeks, 429.45 g/g in those kept for three weeks, and 449.38 g/g in those kept for four weeks. The optimum column temperature was programmed with initial temperature of 40 oC held on for four minutes, then increasing by 40 oC/minute to 200 oC. It can be concluded that the longer the distillates have been kept, the greater the concentration of acetaldehyde in the distillates. A further research to investigate the present of microbe in the distillates and the effect of pH should be conducted.